The manifestations of evil in George Bernard Shaw’s the doctor’s dilemma - Naeem Dwelee, Ali; Mahmood Al-Kamal, Sohaib Kamal; Janoory, Lajiman (Opción, 2019)
This study examines the evil and Machiavellian actions in the health institution in The Doctor’s Dilemma and how man is exploited in the merciless hands of the nefarious doctors via comparative qualitative research methods. As a result, the Shavian solution for the play is adherence to socialism. In conclusion, because of the enormous influence of the environment on the characters, Shaw intentionally shows that morality is a dilemma and thus the reader sees no way of resolving this moral dilemma where even some of the good characters are affected by the environment.